Microstructure and mechanical properties of Al-Si alloys produced by spray forming process - Srivastava V.C.; Mandal R.K.; Ojha S.N. (My University, 2025)
The microstructural characteristics and mechanical properties of Al-6.5Si and Al-18Si alloys have been investigated. The alloys were spray-deposited and hot extruded at 480°C with an area reduction ratio of 6:1. The microstructure of the spray-deposit of Al-6.5Si alloy showed spherical morphology of the primary α-phase with a globular shape of the eutectic Si phase in the inter-particle boundaries. On the other hand, a fine particulate morphology of primary Si phase uniformly dispersed in the matrix of the α-phase was observed in spray-deposit of Al-18Si alloy. Microstructural refinement was further increased in the hot extruded alloys. The room temperature tensile test of spray formed and extruded alloys showed considerable increase in their strength and ductility over that of the as cast alloys. The improvement in mechanical properties of spray formed alloys is discussed in light of the microstructural modifications induced during spray deposition process. © 2001 Elsevier Science B.V. All rights reserved.